How Bridging Social Capital Development Connecting Members of Village Savings and Loan Associations in Community Through Microfinance Activities - Van Toan, Do (VNU Journal of Science: Policy and Management Studies, 2022)
The study indicated how Vietnam Bank for Social Policies’s microfinance activities with Village Savings & Loan Associations model have contributed to the development of social capital in the community. After surveying 356 associations’ members (questionnaire and in-depth interviews), the result showed there has been an increase in social capital; and with it, relationships between members have improved, as evidenced by the formation of self-help groups, increased participation in social organizations, and members' ability to establish relationships and business connections using the human resources acquired via the Vietnam Bank for Social Policies in community. One of the unique and significant findings is the diversity in how the members developed said capacity and how much they have accomplished. This result brings great meaning by demonstrating the effective social impact of the social welfare policies to its beneficiaries. The study also proposed solutions to promote the Vietnam Bank for Social Policies activities and social capital toward a sustainable community development.